The Expression of the Qur’ānic Oaths and Inferences of Imām Qurṭubī (A Specialized Study of Al-Jāmi’ li-Aḥkām al-Qur’ān) - Zunaira Moeez; Muhammad Farooq Haider (jihat-ul-islam, 2021)
An important discussion Of the Qur’ānic Sciences is the Oaths of the Holy Qur’ān which contributes substantially to the linguistic elegance of the Holy Discourse. It is abundant with the ability of effective persuasion. The expression and the intents of the Qur’ānic Oaths are greatly significant in demonstrating the rationale behind them. There are numerous objects (Muqsam) the Exalted Allāh has taken oaths upon, exhibiting their magnificence and esteem. The Oaths of the Qur’ān serve the purpose of auxiliary emphasis to assure the authenticity of their complements (Muqsam ‘Alayh). In this research paper, the meaning and components of the Oath, the expression of the Qur’ānic Oaths, their intents, objects, complements and their interpretation in the light of Al-Jāmi’ li-Aḥkām al-Qur’ān are highlighted with respect to multiple objects of Oaths. Moreover, this paper accentuates the inferences of Imām al-Qurṭubī in elucidation of the Qur’ānic Oaths through descriptive and analytical method and concludes with the styles of expression and motives behind the Oaths taken by the Omnipotent Allāh in the Qur’ān as interpreted in his exegesis.